Microencapsulation of probiotic bacteria: a brief review (Research, Society and Development, 2021)
In the global economic scenario, probiotics have been responsible for a significant financial movement, with progressive growth expected for the coming years. Therefore, the production of dehydrated microbial cultures needs to be optimized, making it necessary to know about the available and already studied techniques. Microencapsulation stands out for enabling the dehydration of microorganisms, protecting cells from the negative effects of drying. This article aimed to compile the literature on the microencapsulation of probiotics, the main encapsulating agents and methods already studied, focusing on drying by atomization. It can be concluded with the consulted literature that the stability and viability of the produced cultures are closely related to the encapsulating agent and the method used for microencapsulation. Further research is needed to explain the protective effect of the conditions used, to direct the optimization of techniques in the production of probiotic cultures that are appropriate for industrial use.